Molecular Characterization and Pathogenicity of the Novel Recombinant Muscovy Duck Parvovirus Isolated from Geese - Kuang-Po Li; Yu-Chen Hsu; Chih-An Lin; Poa-Chun Chang; Jui-Hung Shien; Hsien-Yueh Liu; Hua Yen; Shan-Chia Ou (Animals, 2021)
Goose parvovirus (GPV) and Muscovy duck parvovirus (MDPV) are the main agents associated with waterfowl parvovirus infections that caused great economic losses in the waterfowl industry. In 2020, a recombinant waterfowl parvovirus, 20-0910G, was isolated in a goose flock in Taiwan that experienced high morbidity and mortality. The whole genome of 20-0910G was sequenced to investigate the genomic characteristics of this isolate. Recombination analysis revealed that, like Chinese rMDPVs, 20-0910G had a classical MDPV genomic backbone and underwent two recombination events with classical GPVs at the P9 promoter and partial VP3 gene regions. Phylogenetic analysis of the genomic sequence found that this goose-origin parvovirus was highly similar to the circulating recombinant MDPVs (rMDPVs) isolated from duck flocks in China. The results of experimental challenge tests showed that 20-0910G caused 100% mortality in goose embryos and in 1-day-old goslings by 11 and 12 days post-inoculation, respectively. Taken together, the results indicated that this goose-origin rMDPV was closely related to the duck-origin rMDPVs and was highly pathogenic to young geese.